2020
DOI: 10.1002/ijgo.13196
|View full text |Cite
|
Sign up to set email alerts
|

Cerebro‐placental ratio as a prognostic factor of fetal outcome in pregnancy complicated by maternal sickle cell disease

Abstract: Objectives To assess the role of the cerebro‐placental ratio (CPR) in predicting adverse fetal outcomes among women with sickle cell disease (SCD). Methods A prospective cohort study at Korle‐Bu Teaching Hospital, Accra, Ghana, between January and June 2016. Pregnant women with SCD at 34 gestational weeks or more underwent weekly fetal umbilical and middle cerebral artery Doppler assessment until delivery. Participants were categorized into two study arms based on CPR (<1.1 or ≥1.1). The primary outcome, a com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
(24 reference statements)
1
1
0
Order By: Relevance
“…Consistent with our findings, a study from 2017 at Lady Willingdon Hospital, Lahore, found that the diagnostic accuracy, specificity, sensitivity, positive predictive value, and negative predictive value of the CPR for low APGAR score were 86.94%, 97.18%, 84.21%, 97.64%, respectively [ 16 ]. The cerebroplacental ratio has the highest sensitivity in predicting fetal heart rate anomalies and unfavorable newborn outcomes in term, uncomplicated pregnancies, according to research from Suez Canal University in Ismailia, Egypt [ 17 ].…”
Section: Discussionsupporting
confidence: 89%
“…Consistent with our findings, a study from 2017 at Lady Willingdon Hospital, Lahore, found that the diagnostic accuracy, specificity, sensitivity, positive predictive value, and negative predictive value of the CPR for low APGAR score were 86.94%, 97.18%, 84.21%, 97.64%, respectively [ 16 ]. The cerebroplacental ratio has the highest sensitivity in predicting fetal heart rate anomalies and unfavorable newborn outcomes in term, uncomplicated pregnancies, according to research from Suez Canal University in Ismailia, Egypt [ 17 ].…”
Section: Discussionsupporting
confidence: 89%
“…24 Recent studies have the proven prognostic value of fetal umbilical and middle cerebral artery doppler evaluations in predicting stillbirth and neonatal intensive care unit admission and may be useful for intrapartum planning. 25 There was no overall increased perinatal risk for infants born vaginally to women with HbSS compared to controls, with equal numbers of stillbirths and neonatal deaths seen in the single and multiple vaginal delivery groups. Conversely, there were no stillbirths and fewer neonatal deaths in women with HbSS disease who underwent cesarean delivery.…”
Section: Discussionmentioning
confidence: 87%